Metastatic Uterine Leiomyosarcoma Involving Bilateral Ovarian Stroma without Capsular Involvement Implies a Local Route of Hematogenous Dissemination. (24th May 2015) - Dandapani, Monica; Seagle, Brandon-Luke L.; Abdullah, Amer; Hatfield, Bryce; Samuelson, Robert; Shahabi, Shohreh
Abstract : Uterine sarcomas spread via lymphatic and hematogenous dissemination, direct extension, or transtubal transport. Distant metastasis often involves the lungs. Ovarian metastasis is uncommon. Here we present an unusual case of a large, high-grade uLMS with metastatic disease internal to both ovaries without capsular involvement or other abdominal diseases, and discovered in a patient with distant metastases to the lungs, suggesting likely hematogenous dissemination of uLMS to the ovaries in this case. Knowledge of usual uLMS metastases may influence surgical management in select cases.